Lumbar Plexus Block versus Peri-capsular Injection for Hip Arthroscopy: A Single-Blinded Randomized Controlled Trial. Issue 7 (31st July 2020) - Polmear, Michael; Christensen, Daniel; Salfiti, Catherine; Wolff, Andrew; Scanaliato, John
Objectives: To perform a single-blinded, randomized controlled trial comparing pericapsular injection versus lumbar plexus blockade for post-operative pain control following arthroscopic surgery on the hip. Methods: 70 consecutive patients undergoing hip arthroscopy were prospectively assessed over a six-month period from 2017 to 2018. Patients were randomly allocated to 1 of 2 groups. 35 patients received a lumbar plexus blockade by a single anesthesiologist, while 35 patients received a pericapsular injection of 30cc of ropivacaine and 12mg of morphine. Post-operative pain in the post-anesthesia care unit (PACU) as measured by the numeric rating scale (NRS), time to discharge, PACU morphine equivalents and adverse effects were collected by PACU staff. Post-operative day (POD) 1 and POD 2 narcotic use was obtained through a phone call with the patient on post-operative day 2. Results: We found no statistically significant difference in PACU pain scores at all time-points, although there was a trend towards lower pain for patients receiving a pericapsular injection. PACU and short-term narcotic demand did not differ significantly between the two arms. Time to discharge from the PACU did not differ. There were no major adverse events reported for either intervention. Conclusion: Pericapsular injection provides equivalent analgesia when compared to lumbar plexus injection. It is a safe, time-saving intervention that allows for efficient post-operative analgesia for patients undergoing hip arthroscopy.